2018
DOI: 10.1007/s12094-018-1901-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of psychological differences between adult and elderly cancer patients during postoperative adjuvant chemotherapy

Abstract: Although there were clear psychological differences between adults and senior cancer patients, their evolution during adjuvant chemotherapy was similar, with deterioration in quality of life and coping. This negative psychological impact of adjuvant chemotherapy should be taken into account when considering interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Our results are backed by those of a study carried out in 380 oncological patients at hospitals in northwest England where the younger population expressed a greater need for information about their illness, as well as more emotional, identity, and spiritual concerns than the older ones . Conversely, other studies have revealed that the elderly experience less psychological distress after being diagnosed with cancer, enabling them to adapt better to it . One study performed in Newcastle among adults who had survived childhood cancer showed that their experience with the disease had affected their overall perspectives, giving them a greater appreciation for life and other people, since they had realised that life can be both short and uncertain .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our results are backed by those of a study carried out in 380 oncological patients at hospitals in northwest England where the younger population expressed a greater need for information about their illness, as well as more emotional, identity, and spiritual concerns than the older ones . Conversely, other studies have revealed that the elderly experience less psychological distress after being diagnosed with cancer, enabling them to adapt better to it . One study performed in Newcastle among adults who had survived childhood cancer showed that their experience with the disease had affected their overall perspectives, giving them a greater appreciation for life and other people, since they had realised that life can be both short and uncertain .…”
Section: Discussionsupporting
confidence: 60%
“…15 Conversely, other studies have revealed that the elderly experience less psychological distress after being diagnosed with cancer, enabling them to adapt better to it. 22,23 One study performed in Newcastle among adults who had survived childhood cancer showed that their experience with the disease had affected their overall perspectives, giving them a greater appreciation for life and other people, since they had realised that life can be both short and uncertain. 24 Rosenberg et al concluded that the resilience of young people recently diagnosed with cancer is directly associated with their personal resources and learned abilities: stress management, goal-setting, positive reframing, searching for benefits, social support, and maintaining relationships with relatives and peers.…”
Section: Discussionmentioning
confidence: 99%
“…We purposefully applied maximum variation sampling within this panel to provide an overview of needs that arise at any moment in the disease trajectory. This variation is important because previous research demonstrated that people in different age groups, different stages in the disease trajectory, and with different types of cancer differed in coping styles and psychological distress (Calderón, Jiménez‐Fonseca, Carmona‐Bayonas, & Jara, ; Muñoz‐Sánchez et al, ). Future quantitative research is required to systematically assess whether these differences affect the needs for support that were identified in the present focus group study.…”
Section: Discussionmentioning
confidence: 99%
“…This is also illustrated in an exploratory study by Sodergren et al where young adults with cancer aged 18-25 reported di culties with concentrating when engaging in daily activities because they worried too much about being sick and how it would interfere with their future life plans [6]. Generally, older people with cancer experience less psychological distress after diagnosis, enabling them to better adapt to their activity limitations compared with young adults with cancer [17]. It is somewhat surprising that no differences were found in participation restrictions regarding social functioning between the three age groups, especially as previous research shows that young adults with cancer have di culties with social relations after receiving invasive and long-term cancer treatment [12,34].…”
Section: Results Of Activity and Participationmentioning
confidence: 94%
“…This may cause long-term side effects that in turn, affect the young adults in re-establishing their everyday life [12]. In addition, a number of studies show that people in older age groups with cancer are often more settled in their everyday lives and retain better coping strategies than younger people [15][16][17]. Young adults with cancer may therefore be in a particularly exposed position because they are diagnosed during a period of their life in which they may be establishing relationships and a family, nishing their education or in the early stages of gaining employment [7,12,18,19].…”
Section: Introductionmentioning
confidence: 99%